Dielectric behavior in erbium-doped tellurite glass for potential high-energy capacitor - Muhammad Noorazlan Abd Azis (Tanjong Malim, 2019)
Dielectric behavior in erbium-doped tellurite glass for potential high-energy capacitor by Muhammad Noorazlan Abd Azis